Recovery of Candida dubliniensis and Other Yeasts from Human Immunodeficiency Virus-Associated Periodontal Lesions - Jabra-Rizk, M. A. (American Society for Microbiology, 2001)
Oral and subgingival samples from periodontal lesions were collected from 54 human immunodeficiency virus (HIV)-positive and 20 HIV-negative patients and cultured for yeast species. Of the 54 samples cultured from HIV-positive patients, 44 (82%) were positive for yeast species, of which 29 (66%) were subgingival. A total of 19 (48%) patients were positive for Candida dubliniensis, of which 15 (79%) were colonized in subgingival sites. Seven isolates of Candida glabrata, two isolates of Candida parapsilosis, and one isolate of Saccharomyces cerevisiae were recovered. This study reports for the first time the recovery of C. dubliniensis from subgingival intraoral sites and confirms the presence of Candida species in sites of periodontal disease associated with HIV.